You are on page 1of 3

f(x)=x-2x-3

x=2.0
x=5.0
f(x)f(x)= -36
x=x-((f(x)(x-x))/(f(x)-f(x)))
x= 2. 6
E=((x-x)/x)100
E= 23. 077

x=2.6
f(x)f(x)= -17. 28
x= 2. 8571
E= 9.0

x=2.8571
f(x)f(x)= -6. 6142
x= 2. 9512
E= 3. 1887

x=2.9512
f(x)f(x)= -2. 3138
x= 2. 9836
E= 1. 0859

x=2.9836
f(x)f(x)= -0.78397
x= 2. 9945
E= 0.36461

x=2.9945
f(x)f(x)= -0.26364
x= 2. 9982
E= 0.12224

x=2.9982
f(x)f(x)= -8. 636110
x= 2. 9994
E= 4. 000210

x=2.9994
f(x)f(x)= -2. 879610
x= 2. 9998
E= 1. 333410

x=2.9998
f(x)f(x)= -9. 599510
x= 2. 9999
E= 4. 444510

x=2.9999
f(x)f(x)= -4. 799910
x= 3. 0000
E= 2. 222210a